ANALISIS PENGARUH PENGEMBANGAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) TERHADAP KINERJA PEGAWAI DI RSIA SITTI KHADIJAH 1 MUHAMMADIYAH CABANG MAKASSAR 2023 - Agustina Agustina; Dian Ekawaty; Mohammad Ardani Samad; Nurmulia Wunaini Ngkolu (Institut Kesehatan Pelamonia, 2025)
The Hospital Management Information System (SIMRS) is a computerized system that can manage data quickly and accurately, creating a collection of interactive information that can be used by administrators at all levels in a hospital. RSIA Sitti Khadijah 1 Muhammadiyah Makassar Branch experienced problems related to problems and constraints, one of which was SIMRS user skills. Where sometimes the user forgets and inputs data incorrectly, resulting in a long waiting time for patient services. In addition, there are also network and internet access constraints in the implementation of SIMRS and sometimes there are also devices that suddenly break down, which hinders the performance of the hospital. This study aims to determine and understand the influence of the development of a Hospital Management Information System (SIMRS) on hospital performance at RSIA Sitti Khadijah 1 Muhammadiyah Makassar Branch.The type of research used is quantitative research with a Cross Sectional Study design. This research was conducted with a sample of 104 respondents. The data collection method used in this study was a questionnaire with data analysis techniques using Univariate Analysis and Bivariate Analysis using the chi-square test.The results of this study indicate that there is an influence on hardware development (p=0.001), There is an influence on software development (p=0.003), There is an influence on data development (p=0.044), There is an influence on procedure development (p=0.001), There is an influence on human development (p = 0.000) on employee performance where the p value <0.05. From these results the researcher suggests that training be given related to SIMRS development so that its implementation can further improve performance in hospitals, besides that it can update the features in the SIMRS application so that it can facilitate the SIMRS development process, and can make all units integrated with SIMRS so that the service process at RSIA Sitti Khadijah 1 Muhammadiyah Makassar Branch becomes faster.